COMPARISON OF BLUNT ABDOMINAL TRAUMA SEVERITY SCORING (BATSS) AND CLINICAL ABDOMINAL SCORING SYSTEM (CASS) IN BLUNT ABDOMINAL TRAUMA FOR NEED OF SURGICAL INTERVENTION - SADIA, .; KHALID , OB; ZULFIKAR , I; ALI , R; HUSSAIN , MS; WASEEM , R (Biological and Clinical Sciences Research Journal, 2024)
Blunt abdominal trauma can result in severe intra-abdominal injuries that may necessitate surgery. Scoring systems such as Clinical Assessment Score for Suspected Abdominal Injury (CASS) and Blunt Abdominal Trauma in Severe Spleen Score (BATSS) aid in predicting the need for surgery but require further evaluation. Objective: To assess the efficacy of the CASS and BATSS scoring systems in predicting the necessity of surgical intervention for patients with blunt abdominal trauma. Methods: This comparative study was conducted at Dr. Ruth K. M. Pfau Civil Hospital Karachi from July 1, 2023, to December 31, 2023. Vital signs on admission, signs of abdominal tenderness, distension, guarding, and organ-specific symptoms were recorded for all participants. Diagnostic imaging findings from studies such as abdominal ultrasound, computed tomography (CT) scans, or X-rays were also collected. The study included a total of 185 participants. Statistical analysis included sensitivity and specificity calculations to compare the predictive accuracy of the CASS and BATSS scoring systems. Results: The mean age of the participants was 35.8±12.67 years, with 87% being males. Road traffic accidents were the most common mode of injury (89%). The BATSS scoring system demonstrated higher accuracy in predicting the necessity of surgical intervention after blunting abdominal trauma, with 65.9% sensitivity and 95% specificity compared to the CASS scoring system. Conclusion: The BATSS scoring system shows superior efficacy in predicting the need for surgical intervention following blunt abdominal trauma compared to the CASS scoring system. This suggests that the BATSS score may be a more reliable tool for clinicians in assessing the severity of abdominal injuries and determining the appropriate course of treatment.